TBLT IN PRACTICE: BRINGING TASKS TO ENGLISH CLASSROOM IN THE CURRICULUM 2013 - Aminah Farhatunnisa; Amalul Umam (ENGLISH, 2020)
Task-based language teaching (TBLT) has been one of an approaches used in EFL classrooms due to its effectiveness. It focuses on the authentic language of students in doing meaningful task using the target language. This study investigates the application of TBLT in EFL classroom in the Curriculum 2013. It examines the kind of tasks that can be applied to scaffold students’ writing ability and its effectiveness in scaffolding students’ writing ability. Classroom action research was used in conducting the research in which qualitative data was obtained through observation, interview and documentation. The site of the study was in one of Junior High Schools in Bogor in which class 8 grade was selected. The findings revealed that TBLT can be implemented in the Curriculum 2013 by using different kind of tasks. This study suggests that English teachers may find, modify, and create various kinds of tasks to be implemented in their own classes using TBLT approach.